2000
DOI: 10.1016/s0925-4439(00)00064-8
|View full text |Cite
|
Sign up to set email alerts
|

p-Dimethylaminobenzaldehyde-reactive substances in tail tendon collagen of streptozotocin-diabetic rats: temporal relation to biomechanical properties and advanced glycation endproduct (AGE)-related fluorescence

Abstract: In the present work, pepsin digests of tail tendons from streptozotocin-diabetic rats were found to contain material that reacted rapidly at room temperature with p-dimethylaminobenzaldehyde (Ehrlich's reagent) to give an adduct with an absorbance spectrum characteristic of the Ehrlich chromogen of pyrrolic nature determined in ageing collagens. A significant correlation of the Ehrlich adduct with tendon mechanical strength and collagen fluorescence characteristic of advanced glycation endproducts was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Vessel segments analyzed for ARCC underwent pepsin digestion (43). Briefly, vessel segments were lyophilized for Ͼ8 h to obtain their dry weight.…”
Section: Methodsmentioning
confidence: 99%
“…Vessel segments analyzed for ARCC underwent pepsin digestion (43). Briefly, vessel segments were lyophilized for Ͼ8 h to obtain their dry weight.…”
Section: Methodsmentioning
confidence: 99%
“…Total pepsin digestion was done as described previously [46]. Collagen samples of 10 mg from individual rats were digested with pepsin (50 µg/ml in 0.5 mol/l acetic acid) for 24 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…4 However, the mechanical function of the tendons in this diabetic mouse model has not yet been studied. While studies have revealed the presence of advanced glycation end-products in tendons of diabetic animal models, 28, 29, 33 it is also still unclear if there are changes in other extracellular matrix proteins that could cause changes in mechanical properties, such as proteoglycans or glycosaminoglycans (GAGs). In addition, collagen fiber realignment in response to load, which is indicative of small structural alterations in the tissue, has also not been studied in diabetic tendons.…”
Section: Introductionmentioning
confidence: 99%